Howard Thurman: Spiritual Activist and Mystic of the Movement - Tisby, Jemar (Journal for the study of the historical Jesus, 2019)
This short introduction to the life of Howard Thurman contextualizes his most celebrated book, Jesus and the Disinherited, with attention to the conditions of his childhood, social placement, career, and religious life.